Dirty dancing [videorecording (DVD)] - Ardolino, Emile; Swayze, Patrick; Grey, Jennifer, 1960-; Orbach, Jerry; Rhodes, Cynthia; Bishop, Kelly; Brucker, Jane; Price, Lonny; Weston, Jack, 1924-1996 (Lionsgate, 2010)
An innocent young girl is introduced to the sensuality of dance when she meets the dance instructor at her resort hotel.